Cochlear implants with fine structure processing improve speech and tone perception in Mandarin-speaking adults. (July 2013) - Chen, Xueqing; Liu, Bo; Liu, Sha; Mo, Lingyan; Li, Yuling; Kong, Ying; Zheng, Jun; Li, Yongxin; Gong, Shusheng; Han, Demin
Abstract Conclusion: This study indicates that Mandarin-speaking subjects acquire significant benefit from a cochlear implant (CI) and audio processor with the fine structure processing (FSP) coding strategy. It can take adult Mandarin CI users time to become accustomed to their CI and appreciate the benefits. Objectives: This study aimed to determine speech perception outcomes in Mandarin-speaking adults who received the FSP coding strategy. Methods: This was a prospective study. Ten adults who were implanted unilaterally with a PULSARCI100, and received an OPUS 1 or OPUS 2 speech processor, were included in this study. The mean age at implantation was 31.1 years. We determined the benefit to postlingually deafened Mandarin-speaking adults with a severe to profound hearing loss using the tests: monosyllables in quiet, sentences in quiet and the Mandarin Hearing in Noise Test (MHINT). Tone perception was evaluated using a tone perception test. A visual analog scale (VAS) was used to score sound quality and ease of listening. Results: The results showed a significant improvement between first fitting and 6 months in all speech tests and in tone perception. The VAS scores showed a significant improvement over 6 months in sound quality and an immediate benefit in ease of listening.